PROTEIN CARBONYL AND LIPID HYDRO PEROXIDES AS PUTATIVE BIOMARKERS IN PATIENTS WITH CERVICAL AND OVARIAN CARCINOMA - SUMAN GAUTAM; A .A. MAHDI; RANJANA SINGH; SEEMA MEHROTRA (International Journal of Pharma and Bio Sciences, 2014)
The present study was conducted in patients with cervix and ovarian carcinoma to evaluate the status of oxidative stress biomarkers as protein carbonyl and lipid hydro peroxides. Biomarkers of oxidative stress were measured as protein carbonyl (PC) and total lipid hydro peroxides (LOOH). Newly diagnosed women with carcinoma (n=100; 30-65 years of age) and age- matched clinically healthy women (n=50) were included in the present study. Circulating plasma total lipid hydro peroxides and protein carbonyl levels were significantly (p<0.05) higher in patients as compared to controls. The application of protein carbonyl and lipid hydro peroxides as biomarkers of oxidative stress has some advantages in comparison with measurement of other oxidation products because of the relative early formation and relative stability. Elevation of protein carbonyl and lipid hydroperoxides reflect oxidative stress in carcinoma patients and might be helpful in management of such patients.